Pengaruh Pendekatan Konflik Kognitif Terhadap Pemahaman Konsep Pada Materi Gerak Lurus - Sutrio Sutrio; Muhammad Makhrus; Armi Larasati (-)
This study aims to determine the effect of the cognitive conflict approach on the conceptual understanding of senior high school students in class X on straight motion material. This type of research is a pre-experimental research design with One Group Pretest-Posttest Design. The population in this study were all students of class X MIPA State Senior High School 1 Narmada. The research sample was obtained using a positive sampling technique, obtained class X MIPA 1 as experimental class 1, class X MIPA 2 as experimental class 2, and class X MIPA 3 as experimental class 3. Data collection on conceptual understanding used multiple-choice tests of 15 questions. Hypothesis test analysis used a statistical paired sample t-test and showed that Ho was rejected and Ha was accepted. This shows that the cognitive conflict approach affects students' conceptual understanding of straight motion material.